The effects of ankle Kinesiotaping on postural control in healthy taekwondo athletes - Yasemin Bayraktar; Nurtekin Erkmen; Yagmur Kocaoglu; Bayram Sönmez Ünüvar (Physical Education of Students)
Background and Study Aim. Although Kinesiotape is widely used by athletes, information about its effect is unclear. Its effect on postural control might directly affect an athlete's performance. In this study, it is aimed to find out whether ankle Kinesiotaping in taekwondo athletes affects postural control.